USING PROJECT-BASED LEARNING WORKSHEET WITH WASTE WATER TREATMENT THEME TO PRACTICE STUDENT’ PROBLEM-SOLVING SKILLS - Angelia Kartika Cahyasari; Mohammad Budiyanto; Enny Susiyawati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aimed to describe the use of a Project-Based Learning worksheet for grade VII students in order to facilitate practising problem-solving skills. The research design of this study was one group pretest-posttest design. The worksheet was distributed to 30 students at Junior High School 18 Surabaya. The research method used the test method that is a pretest-posttest, in the form of essays that include indicators of problem-solving skills. Based on the results of research from the students' pretest and posttest scores, the average value of the increase in N-gain of all students was 0.67 with the medium category. Meanwhile, based on the results of the average value of the increase in N-gain of all indicators of students' problem-solving skills obtained results of 0.67 with a high category. Based on the results of the study, it can be concluded that develop worksheet Project-Based Learning for students to practice problem-solving skills was effective.